Fascicular torsions of the anterior and posterior interosseous nerve in 4 cases: neuroimaging methods to improve diagnosis - Hayes, Jennifer; Preisser, Paul; Bendszus, Martin; Kele, Henrich (Journal of neurosurgery, 2020)
Diagnosis of spontaneous fascicular nerve torsions is difficult and often delayed until surgical exploration is performed. This case series raises awareness of peripheral nerve torsions and will facilitate an earlier diagnosis by using nerve ultrasound (NUS) and magnetic resonance neurography (MRN). Four patients with previously ambiguous upper-extremity mononeuropathies underwent NUS and 3T MRN. Neuroimaging detected proximal torsions of the anterior and posterior interosseous nerve fascicles within median or radial nerve trunks in all patients. In NUS, most cases presented with a thickening of affected nerve fascicles, followed by an abrupt caliber decrease, leading to the pathognomonic sausage-like configuration. MRN showed T2-weighted hyperintense signal alterations of fascicles at and distal to the torsion site, and directly visualized the distorted nerves. Three patients had favorable outcomes after being transferred to emergency surgical intervention, while 1 patient with existing chronic muscle atrophy was no longer eligible for surgery. NUS and MRN are complementary diagnostic methods, and both can detect nerve torsions on a fascicular level. Neuroimaging is indispensable for diagnosing fascicular nerve torsions, and should be applied in all unclear cases of mononeuropathy to determine the diagnosis and if necessary, to guide surgical therapies, as only timely interventions enable favorable outcomes.